Trends in Comparative Endocrinology and Neurobiology - Hubert Vaudry (Frontiers Research Topics, 2018)
The comparative approach takes advantage of the biological diversity to select the most appropriate model organism to tackle a scientific question. Comparisons between the endocrine and nervous systems accross species have yielded major breakthroughs in endocrinology and neurobiology. For instance: a number of mammalian peptide hormones and neuropeptides have been originally identified in fish or amphibians; studies conducted in a sea slug founded the cellular and molecular basis of learning and memory; observations of neurogenesis in the forebrain of songbirds led to the discovery of adult neurogenesis in the mammalian brain. These examples illustrate the remarkable contribution of the comparative approach for the advancement of neuroendocrinological concepts. The present e-book is a unique collection of research articles and reviews that provide a representative overview of the latest developments in comparative endocrinology and neurobiology.